MANAJEMEN SUMBER DAYA MANUSIA DI LEMBAGA PENDIDIKAN ISLAM - Rohayati; Isdaryanti, Barokah; sutarto, joko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Human Resource Management (HRM) is a key element in determining the quality and sustainability of Islamic educational institutions amidst the challenges of globalization and digitalization. This study aims to analyze and explore the implementation of HRM practices in three different educational institutions: MAN 1 Surakarta, MAN 3 Sukabumi, and SDI Al Azhar Tulungagung. The method used is a comparative analysis of relevant previous research findings, focusing on the management cycle from planning to evaluation. The results of the analysis indicate that all three institutions have implemented management functions systematically through strategic planning as outlined in RKM/Renstra documents, recruitment that integrates professional competence with moral and religious standards, and staff placement based on the principle of the right man in the right place. Continuous professional development for teachers is conducted through formal training (workshops/MGMP) and cultural-spiritual guidance to maintain loyalty and work motivation. Specific findings show that in inclusive schools, HRM is optimized by recruiting specialized experts, such as psychologists or special education graduates, to ensure quality services for students with special needs. Overall, the synergy between professional management and the strengthening of Islamic values serves as the primary foundation for enhancing organizational performance and educational quality in Islamic institutions.